Trade consistency in the context of the Eurosystem projection exercises – an overview - Kirstin Hubrich; Tohmas Karlsson (European Central Bank (ECB), 2010)
The Eurosystem macroeconomic projection exercises are part of the input prepared for the Governing Council's decision-making meetings. Under the economic analysis pillar of the ECB's monetary policy strategy, they are a key element in the assessment of economic prospects and of the short to medium-term risks to price stability. The projection exercises are conducted on the basis of a number of “technical” assumptions. In particular, assumptions are made about future developments in world trade, foreign prices and nominal exchange rates. The purpose of the trade consistency exercise (TCE) is to ensure that individual country forecasts are consistent with each other regarding the assumptions made about the international environment. Trade consistency is ensured in two directions: first, the cross-trade consistency part of the TCE involves examining the consistency of the trade projections at any given point in time; and second, the ex ante/ex post trade consistency part involves comparing the projections for a given variable across different projection rounds. This paper provides a comprehensive description of the data and techniques underlying the trade consistency exercises in the context of the projection exercises of the Eurosystem and the ECB.
Keywords: C23; D92; E22; E52; G31; G32; 330; competitiveness; cross-country consistency; market shares; Trade projections